Inanimate 3D printed model for thoracoscopic repair of esophageal atresia with tracheoesophageal fistula - Zahradniková, Petra; Babala, Jozef; Pechanová, Rebeka; Smrek, Martin; Vitovič, Pavol; Laurovičová, Miroslava; Bernát, Tomáš; Nedomová, Barbora (Frontiers in Pediatrics, 2023)
Inanimate 3D Printed Model for Thoracoscopic Repair of Esophageal Atresia with Tracheoesophageal Fistula Abstract Background Thoracoscopic esophageal atresia (EA)/tracheoesophageal fistula (TEF) repair is technically challenging. The purposes of this study were to create an inexpensive, reusable, high-fidelity synthetic tissue EA/TEF repair simulation model and to evaluate the validity of this simulator. Method We have developed a new inanimate inexpensive easy reusable model designed for training of thoracoscopic repair of EA/TEF. The goal of this study was to validate this model using 5-point Likert scale validation and objective structured assessment of technical skills (OATS) for participants’ surgical performance. Results A total of 17 participants after instructions and training were asked to perform TEF ligation, dissection and esophageal anastomosis using six sliding knots on the EA/TEF simulator. Six medical students, 4 pediatric surgery trainees and 7 experienced surgeons were enrolled in this study. All participants in the consultant group completed the task within the allotted 120-min period; however, only one participant from inexperienced group completed the task within the time limit. There was a statistically significant difference in OSATS scores for the ‘flow of task’ (p = 0.018) and scores for the ‘MIS skills’ (p = 0.010) task distinguishing between novice and intermediates and experts. The simulator showed good content validity; its usefulness as a training tool for EA/TEF, with the mean score of 4.68. The mean scores for realism of the model and working environment were 4.25 and 4.5, respectively. Conclusions Our study demonstrated good face and content validity. As our model is inexpensive, reusable, easily replaceable for each participant it seems to as that it holds real potential as a thoracoscopic training device for surgeons. However, novices and trainees were not able to finished advanced MIS procedure. Therefore, a structured and focused training curriculum in pediatric MIS is needed for optimal utilization of the available training hours.